Field Trip Strategy in Enhancing Writing Descriptive Text - rugaiyah rugaiyah (UIR Press, 2017)
Field-based learning has long been used by teachers to enhance students learning. Futher, Field trips are recognized as important moments in learning; a shared social experience that provides the opportunity for students to encounter and explore novel things in an authentic setting. The need to develop an effective environmental education program ranks as one of the major challenges facing education in the next decade. This paper is focused on analyzing the effectiveness of field trips strategy on students’ writing descriptive text for a group of 30 students of second semester of FKIP UIR Pekanbaru in academic year 2016/2017 who were selected by using random sampling. The data were collected by giving test (pre-test and post-test) This study used experimental reseacrch, used by the Mann-Whitney U t-test. The normality of the test was analysed through Kolmogorov-Smirnova..The instruments used in this study were lesson plans and writing descriptive text tests. Regarding the data analysis, mean, percentage and Mann-Whitney U test scores for the dependent sample were employed. The result of statistc indicated that the asymptotic significance of less than 0.05 (p = 0.00 < 0.05). it means the students’ ability in writing descriptive text increased significantly after learning with fild trip strategy.